Correlation of tribo-mechanical properties of internal geometry structures of fused filament fabrication 3D-printed acrylonitrile butadiene styrene - Norani, Mohamad Nordin Mohamad; Abdollah, Mohd Fadzli Bin; Abdullah, Muhammad Ilman Hakimi Chua; Amiruddin, Hilmi; Ramli, Faiz Redza; Tamaldin, Noreffendy (Industrial lubrication and tribology, 2020)
Purpose This study aims is to investigate the correlation between tribological and mechanical properties of the fused filament fabrication 3D-printed acrylonitrile butadiene styrene (ABS) pin with different internal geometries. Design/methodology/approach The tribological properties were determined by a dry sliding test with constant test parameters, while the hardness and modulus of elasticity were determined by microhardness and compression tests. Findings Although the internal geometry of the pin sample slightly affects the coefficient of friction (COF) and the wear rate of the 3D-printed ABS, it was important to design a lightweight tribo-component by reducing the material used to save energy without compromising the strength of the component. The COF and wear rate values are relatively dependent on the elastic modulus. A 3D-printed ABS pin with an internal triangular flip structure was found to have the shortest run-in period and the lowest COF with high wear resistance. Abrasive wear and delamination are the predominant wear mechanisms involved. Research limitations/implications The findings are the subject of future research under various sliding conditions by investigating the synergistic effect of sliding speeds and applied loads to validate the results of this study. Originality/value The internal structure affects the mechanical properties and release stress concentration at the contact point, resulting in hypothetically low friction and wear. This approach may also reduce the weight of the parts without scarifying or at least preserving their preceding tribological performance. Therefore, based on our knowledge, limited studies have been conducted for the application of 3D printing in tribology, and most studies focused on improving their mechanical properties rather than correlating them with tribological properties that would benefit longer product lifespans. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-04-2020-0143/